Migration, pathogens and the avian microbiome: A comparative study in sympatric migrants and residents. Issue 23 (19th October 2020) - Turjeman, Sondra; Corl, Ammon; Wolfenden, Andrew; Tsalyuk, Miriam; Lublin, Avishai; Choi, Olivia; Kamath, Pauline L.; Getz, Wayne M.; Bowie, Rauri C. K.; Nathan, Ran
Abstract: Animals generally benefit from their gastrointestinal microbiome, but the factors that influence the composition and dynamics of their microbiota remain poorly understood. Studies of nonmodel host species can illuminate how microbiota and their hosts interact in natural environments. We investigated the role of migratory behaviour in shaping the gut microbiota of free‐ranging barn swallows ( Hirundo rustica ) by studying co‐occurring migrant and resident subspecies sampled during the autumn migration at a migratory bottleneck. We found that within‐host microbial richness ( α ‐diversity) was similar between migrant and resident microbial communities. In contrast, we found that microbial communities (β‐diversity) were significantly different between groups regarding both microbes present and their relative abundances. Compositional differences were found for 36 bacterial genera, with 27 exhibiting greater abundance in migrants and nine exhibiting greater abundance in residents. There was heightened abundance of Mycoplasma spp. and Corynebacterium spp. in migrants, a pattern shared by other studies of migratory species. Screens for key regional pathogens revealed that neither residents nor migrants carried avian influenza viruses and Newcastle disease virus, suggesting that the status of these diseases did not underlie observed differences in microbiome composition. Furthermore, the prevalence and abundance of Salmonella spp., as determined from microbiome data and cultural assays, were both low and similar across the groups. Overall, our results indicate that microbial composition differs between migratory and resident barn swallows, even when they are conspecific and sympatrically occurring. Differences in host origins (breeding sites) may result in microbial community divergence, and varied behaviours throughout the annual cycle (e.g., migration) could further differentiate compositional structure as it relates to functional needs.